Game-Based Learning Mobile Application About Orang Asli - Wan Mohd Isa, Wan Abdul Rahim; Suhaimi, Ahmad Iqbal Hakim; Noordin, Nurulhuda; Mohd Azhar, Muhammad Nazril Afiq (Journal of Advanced Research Design, 2025)
This study presents the design and development of a mobile game-based learning application in the form of a visual novel, created to promote cultural understanding and empathy toward the Indigenous People (Orang Asli) in Malaysia. The application, entitled 16 Hari Bersama Orang Asli (16 Days with the Indigenous People), integrates interactive storytelling, user decision-making, and visually engaging character designs to provide an immersive learning experience. A user persona was constructed to guide design decisions, while flowcharts and use case diagrams structured the narrative pathways and gameplay mechanics. The resulting application offers multiple story endings based on player choices, encouraging active participation and reflective learning. Although limitations remain in terms of graphics, language support, and representation of Orang Asli tribes, the application demonstrates significant potential as an educational platform. By combining entertainment with cultural education, this study highlights the role of mobile game-based learning in preserving indigenous heritage, fostering inclusivity, and enhancing cultural appreciation among young adults. Future improvements, including cross-platform expansion and closer collaboration with Orang Asli communities, will further enrich its authenticity and impact.